Mitigation effects of plant carbon black on intestinal morphology, inflammation, antioxidant status, and microbiota in piglets challenged with deoxynivalenol - Wu, Jie; Wang, Hanyang; Liao, Jianling; Ke, Linfu; Lu, Deqiu; Deng, Bo; Xu, Ziwei (Frontiers in Immunology, 2024)
Plant carbon black (PCB) is a new feed additive for zearalenone adsorption in China. However, information regarding whether PCB can effectively absorb deoxynivalenol (DON) is limited. To explore this research gap, the present study examined the adsorption effectiveness of DON by PCB using a phosphate buffer, artificial gastric juice, and artificial intestinal juice. In a 21d in vivo trial, 48 male piglets were randomly assigned to four treatment groups: (1) uncontaminated basal diet (CTR),(2) basal diet supplemented with 1 mg/kg PCB(PCB), (3) 2.3 mg/kg DON-contaminated diet (DON), and (4) 2.3 mg/kg DON-contaminated diet supplemented with 0.1% PCB (DON+PCB). When DON concentration was 1 μg/mL, the adsorption rate of PCB on DON in phosphate buffer systems (pH 2.0 and 6.0) and the artificial gastric and intestinal juices were 100, 100, 71.46, and 77.20%, respectively.In the in vivo trial, the DON group significantly increased the DON+deepoxy-deoxynivalenol(DOM-1) content in serum as well as the inflammation cytokine proteins (interleukin-6, interleukin-8, tumor necrosis factor-α) and mRNA expression of interleukin-6, long-chain acyl-CoA synthetase 4 in jejunum and ileum. It decreased the villus height, goblet cells, mucosal thickness, and mRNA expression of Claudin-1 compared to the CTR group. In addition, DON decreased the Shannon and Simpson indices, reduced the relative abundances of Firmicutes, Lactobacillus, Candidatus_Saccharimonas, and Ruminococcus, and increased the relative abundances of Terrisporobacter and Clostridium_sensu_stricto_1 in the cecal content. PCB interestingly mitigated DON-induced changes in intestinal morphology, mucosal inflammation, antioxidant status, and cecal microbiota. In conclusion, these results confirm the protective effects of PCB against various intestinal toxicity manifestations in DON-challenged piglets.